STRATEGI PEMBELAJARAN AL-QURAN HADIS DI ERA SOCIETY 5.0 - RITMAN HENDRA (Piwulang: Jurnal Pendidikan Agama Islam, 2022)
Al-Quran Hadith is one of the subjects in the Islamic Religious Education (PAI) and Arabic language, this subject is important to learn without reducing the importance of other subjects that are still in the same family or other general subjects being taught. This article aims to provide strategies for finding appropriate and relevant patterns related to the development of science and technology, times have changed towards the era of society 5.0. Change is a strategy used by the tutors of Al-Quran Hadith subjects while continuing to update their knowledge to deal with changes, which changes cannot be restrained and inhibited. So that students have the stimulation to study the Al-Quran Hadith to make them become people who give benefit to themselves, their families, and society at large, case by case in this country can be minimized through students' understanding of the Koran and Hadith. The research is in the form of library research using a descriptive qualitative approach, and techniques for collecting data through various articles and relevant books. then a descriptive analysis is carried out, and finally, conclusions are made. The result of this article is a strategy that must be owned by educators that is adapted to the times they are facing, especially the subjects of the Koran Hadith as the main guideline for Muslims.